Nephrology intervention to avoid acute kidney injury in patients awaiting cardiac surgery: randomized clinical trial - Sergi Codina; Sergi Codina; Laia Oliveras; Laia Oliveras; Eva Ferreiro; Aroa Rovira; Ana Coloma; Nuria Lloberas; Edoardo Melilli; Miguel Hueso; Miguel Hueso; Fabrizio Sbraga; et al. (Frontiers in Nephrology)
IntroductionCardiac surgery-associated acute kidney injury (CSA-AKI) is a well-known complication that increases morbidity and mortality rates. The objective of this study was to reduce CSA-AKI through nephrologist intervention in patients awaiting cardiac surgery.MethodsWe performed a single center, open-label, randomized clinical trial including 380 patients who underwent scheduled cardiac surgery at the Hospital de Bellvitge between July 2015 and October 2019. A total of 184 patients were evaluated by the same Nephrologist one month before the surgery to minimize the risk factors for AKI. In addition to assessments at the outpatient clinic, we also collected clinical data during hospitalization and during the first year.ResultsDespite the intervention, no differences were observed between the groups in the incidence of CSA-AKI (intervention group 26.37% vs. standard of care 25.13%, p=0.874), mortality (3.91% vs. 3.59%, p=0.999), length of Intensive Care Unit (ICU) stay (10 days [7.00;15.0] for both groups, p=0.347), or renal function after one year of follow-up (estimated glomerular filtration rate (eGFR) by CKD-EPI: 74.5 ml/min (standard deviation 20.6) vs 76.7 (20.8) ml/min, respectively, p=0.364). A reduction in the need for blood transfusion was observed in the intervention group, although the difference was not statistically significant (37.22% vs. 45.03%, p =0.155).ConclusionIn this clinical trial, nephrologist intervention in the entire population on the cardiac surgery waiting list did not show a nephroprotective benefit.Clinical trial registrationClinicalTrials.gov, identifier (NCT02643745).